PENGARUH GOOD CORPORATE GOVERNANCE DAN AUDIT FIRM SIZE TERHADAP FIRM VALUE - Prasetyo, Eko Heru (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
Globalization in business has pushed companies to conduct a good way in controlling its organization which is done by implementing Good Corporate Governance (GCG). Every company is trying to disclose its fairness financial statement helped by Certified Public Accountant (CPA) to attract investor. This research aims to determine the effect of Good Corporate Governance mechanisms; audit committee, board of commissioner, and proportion of independent commissioner on firm value, and the effect of Audit Firm Size on Firm Value. Firm Value is shown by Tobinâs Q ratio which compares Equity Market Value (EMV) and Equity Book Value (EBV). Sample in this research is 24 banking company listed in Indonesia Stock Exchange from 2010 until 2012. This research use quantitative approach with descriptive purpose by observing 106 items of banking companyâs financial statement and summary of company report. This research use data panel regression which combine cross section and time series data with one dummy variable, Audit Firm Size, and classical assumption test. The results show that (1) Good Corporate Governance mechanisms do not affect on Firm Value, (2) Audit Firm Size does not affect on Firm Value. On the other hand, Firm Value banking company is affected by its Firm Value on previous period because of inefficiency market applied Indonesia. Investors still use historical data based on financial statement to predict the price of companyâs stock.